Examination of peripheral basal and reactive cortisol levels in major depressive disorder and the burnout syndrome: A systematic review. (July 2020) - Rothe, N.; Steffen, J.; Penz, M.; Kirschbaum, C.; Walther, A.
Highlights: There is considerable overlap in the dimensions of symptoms of major depressive disorder (MDD) and the burnout syndrome. A dysregulation of the HPA axis as a central stress-physiological system has been related to both conditions separately. For MDD, findings suggest a general state of hypercortisolism and glucocorticoid-resistance. A clear overweight of studies examining MDD and cortisol were identified compared to studies focusing on burnout. For burnout, no clear conclusion could be drawn due to small amount of available studies and heterogeneity in assessment. Abstract: It is debated as to whether major depressive disorder (MDD) and the burnout syndrome represent different aspects of the same syndrome or whether they reflect separate entities. A dysregulation of the hypothalamus-pituitary-adrenal-axis has been related to both conditions separately. Dissecting the pathophysiology of the conditions and describing differences and similarities with regard to stress physiological systems might further clarify whether underlying etiological models of these syndromes differ. A systematic literature search including MDD and the burnout syndrome and peripheral cortisol measures was performed and resulted in 190 studies for inclusion in the qualitative synthesis. For MDD, findings suggest a general state of hypercortisolism and glucocorticoid resistance reflected by increased basal cortisol levels, reduced reactivity to psychosocial stress and a reduced cortisol suppression in pharmacological challenge tests. For the burnout syndrome, two central factors limit further conclusions: i) there is not a sufficient amount of studies examining the burnout syndrome and different cortisol secretion patterns to provide an evidence base, ii) the burnout syndrome is assessed heterogeneously reflecting imprecision of the measured constructs. Large prospective cohort studies examining both conditions in parallel rigorously controlling for confounders are required to further elucidate the differences and similarities of the HPA axis in MDD and the burnout syndrome.